2021
DOI: 10.3390/su131910592
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting Overtourism Using Demarketing Tools: A Logit Analysis Based on Existing Literature

Abstract: Over the past few decades, demarketing has come up as an unorthodox but potentially strong approach that can be used to counter the negative effects of oversaturation in tourism destinations. This study investigates the difference that demarketing strategies can make on mitigation efforts towards overtourism in destinations across the globe by conducting a meta-analysis of the previous literature examining various case studies on the topic. This study approaches demarketing efforts against overtourism through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…While the number of tourists per km2 has been multiplied by a factor of 1.6 at the regional level, Funchal experienced an increase of just 40%, with some areas such as Calheta experiencing a noticeable increase. Regardless of the indicator used to determine excess visitors levels, such as the carrying capacity, local resident dissatisfaction or tourist satisfaction and environmental degradation, Madeira cannot be considered as a classic example of an overcrowded area, as mentioned before, at least from a journalistic and visual perspectives, but for a few exceptions [17]. However, a recent study commissioned by the Office of the Ombudsman [67] indicated that Funchal, the main capital city, has been affected by the impacts of tourism in terms of the local lodgment format, housing prices and housing affordability in relation to the local population's income levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the number of tourists per km2 has been multiplied by a factor of 1.6 at the regional level, Funchal experienced an increase of just 40%, with some areas such as Calheta experiencing a noticeable increase. Regardless of the indicator used to determine excess visitors levels, such as the carrying capacity, local resident dissatisfaction or tourist satisfaction and environmental degradation, Madeira cannot be considered as a classic example of an overcrowded area, as mentioned before, at least from a journalistic and visual perspectives, but for a few exceptions [17]. However, a recent study commissioned by the Office of the Ombudsman [67] indicated that Funchal, the main capital city, has been affected by the impacts of tourism in terms of the local lodgment format, housing prices and housing affordability in relation to the local population's income levels.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence available suggests that residents welcome tourism if they can benefit directly or indirectly from it [6,16]. If politicians are well aware and conscious of this situation, they can implement measures to redirect and disperse tourists to less-known attractions based on the development of "new tourist routes" in the rural periphery to ensure the right densities of tourists both in the core and peripheral areas ( [17], p. 1). In theory, this approach can generate higher levels of fairness and justice and degrowth (in the existing core areas) in a socially sustainable way [20].…”
Section: Literature Review: From Overtourism To Opportunities To Prom...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some leaflets in the research did not contain the most famous sites at all. They are the result of a recent trend in which the regions are trying to do so-called demarketing (see Hall & Wood 2021, Gulsen et al 2021, Drugova, Kim & Jakus 2021 in order to avoid overtourism in these localities.…”
Section: Resultsmentioning
confidence: 99%
“…Some leaflets in the research did not contain the most famous sites at all. They are the result of a recent trend in which the regions are trying to do so-called demarketing (see Hall & Wood 2021, Gulsen et al 2021, Drugova, Kim & Jakus 2021 in order to avoid overtourism in these localities.…”
Section: First Phasementioning
confidence: 99%